Schauder Basis, Separability, and Approximation Property in Intuitionistic Fuzzy Normed Space - M. Mursaleen; V. Karakaya; S. A. Mohiuddine (Abstract and Applied Analysis)
We define and study the concepts of Schauder basis, separability, and approximation property in intuitionistic fuzzy normed spaces and establish some results related to these concepts. We also display here some interesting examples by using classical sequence spaces ℓ𝑝(1≤𝑝≤∞).